2012
DOI: 10.1681/asn.2012040389
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Primary FSGS in Adults

Abstract: Over the last 20 years, primary FSGS has emerged as one of the leading causes of idiopathic nephrotic syndrome in adults, particularly among African Americans. In nephrotic patients, progression to ESRD often occurs over the course of 5-10 years, whereas non-nephrotic patients and those entering a remission have an extremely favorable prognosis. As a result, it is in patients who remain persistently nephrotic despite conservative therapy that a more aggressive therapeutic approach is taken. Primary FSGS was on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
138
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(144 citation statements)
references
References 76 publications
1
138
0
5
Order By: Relevance
“…These therapies are summarized in Tables 4 and 5 and discussed below. A comprehensive analysis of approaches to steroid-sensitive and -resistant FSGS is available from the Kidney Diseases Improving Global Outcomes initiative, and the reader is referred to this initiative for a detailed and thoughtful discussion (100) as well as recent reviews (13). FSGS may be responsive to therapy with glucocorticoids, although relapses are typical.…”
Section: Therapeutic Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…These therapies are summarized in Tables 4 and 5 and discussed below. A comprehensive analysis of approaches to steroid-sensitive and -resistant FSGS is available from the Kidney Diseases Improving Global Outcomes initiative, and the reader is referred to this initiative for a detailed and thoughtful discussion (100) as well as recent reviews (13). FSGS may be responsive to therapy with glucocorticoids, although relapses are typical.…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…Many other agents have been tested in small trials or reported as case series, and they have been the subject of recent reviews (13,(108)(109)(110)(111). These agents include the following: adalimumab, an anti-TNF mAb (112); pirfenidone, an antifibrotic agent that suppresses TGF-b signaling (113); fresolimumab, an anti-TGF-b mAb (114); pulse steroids plus cyclophosphamide (115); and saquinivir (116).…”
Section: Therapeutic Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…), bu tedavinin yanında steroid tedavisi tek başına veya immünsüpresif ajanlarla kombine (CsA, mikofenolat mofetil, azotiopürin, takrolimus, siklofosfamid vb.) kullanılmaktadır (3,5,7).…”
Section: Yöntemlerunclassified
“…Tedaviye yanıt alınamayan olgularda immünsüpresif tedavi uygulanmaktadır (steroid, kalsinörin inhibitörleri, mikofenolat mofetil vb.). Remisyona giren hastalarda genel sağkalım %90 iken, remisyona girmeyenlerde bu oran %35'in altındadır (5).…”
Section: Introductionunclassified